Experience with a once-daily aminoglycoside program administered to 2,184 adult patients. - Nicolau, D P (1995)
Once-daily aminoglycoside (ODA) regimens have been instituted to maximize bacterial killing by optimizing the peak concentration/MIC ratio and to reduce the potential for toxicity. We initiated an ODA program at our institution that utilizes a fixed 7-mg/kg intravenous dose with a drug administration interval based on estimated creatinine clearance: > or = 60 ml/min every 24 h (q24h), 59 to 40 ml/min q36h, and 39 to 20 ml/min q48h. Subsequent interval adjustments are made by using a single concentration in serum and a nomogram designed for monitoring of ODA therapy. Since initiation of the program, 2,184 patients have received this ODA regimen. The median dose was 450 (range, 200 to 925) mg, while the median length of therapy was 3 (range, 1 to 26) days. The median age of the population was 46 (range, 13 to 97) years. Gentamicin accounted for 94% of the aminoglycoside use, and the majority (77%) of patients received the drug q24h. The 36-, 48-, and > 48-h intervals were used for 15, 6, and 2% of this population, respectively. Three patients exhibited clinically apparent ototoxicity. Twenty-seven patients (1.2%) developed nephrotoxicity (the Hartford Hospital historical rate is approximately 3 to 5%) after a median of 7 (range, 3 to 19) days of therapy. On the basis of a prospective evaluation of 58 patients and follow-up of additional patients via clinician reports, we have noted no apparent alterations in clinical response with our ODA program. This ODA program appears to be clinically effective, reduces the incidence of nephrotoxicity, and provides a cost-effective method for administration of aminoglycosides by reducing ancillary service time and serum aminoglycoside determinations.